Automated scoring for elite half-pipe snowboard competition: important sporting development or techno distraction? - Harding, J. W.; Mackintosh, C. G.; Martin, D. T.; Hahn, A. G.; James, D. A. (Sports Technology, 2008)
We previously reported a strong relationship between video-based objectivedata (air time and degree of rotation) and subjectively-judged scoresawarded during elite half-pipe snowboard competitions. Advancements insport-monitoring technologies now provide the capacity to accurately andautomatically quantify this objective information. This may assist currentsubjective coaching and competition judging protocols provided theintegration process imparts a large element of control to key players withinthe sport. We therefore recently hosted an invitational half-pipe snowboardcompetition (2007 Australian Institute of Sport Micro-Tech PipeChallenge) designed to evaluate whether the snowboarding community wouldembrace a competition where results were in part determined by automatedobjectivity. We explored the practical, logistical, and technical challengesassociated with conducting such an event and evaluated the relationshipbetween subjective judging and results predicted from objective informationto see if prior research had ecological validity. Ten elite, male half-pipesnowboarders were instrumented with inertial sensors throughout thiscompetition. A prediction equation using previously-established weightings ofaverage air time and average degree of rotation accounted for 74 per cent ofthe shared variance in subjectively-judged scores awarded during thiscompetition. Although our predictions of overall scores and rankings weregood, 26 per cent of the total variance was still unexplained. This should notbe considered a weakness of this approach, but a strength, as the subjectivecomponents of style and execution should never be removed from the sport.The future of half-pipe snowboarding, however, may be best guided a judgingprotocol that incorporates both objective and subjective criteria.